Anatomical and functional plasticity in early blind individuals and the mixture of experts architecture - Bock, Andrew S.; Fine, Ione (Frontiers in Human Neuroscience, 2014)
As described elsewhere in this special issue, recent advances in neuroimaging over the last decade have led to a rapid expansion in our knowledge of anatomical and functional correlations within the normal and abnormal human brain. Here, we review how early blindness has been used as a model system for examining the role of visual experience in the development of anatomical connections and functional responses. We discuss how lack of power in group comparisons may provide a potential explanation for why extensive anatomical changes in cortico-cortical connectivity are not observed. Finally we suggest a framework – cortical specialization via hierarchical mixtures of experts – which offers some promise in reconciling a wide range of functional and anatomical data.